MOTIVASI BELAJAR PESERTA DIDIK MATAKULIAH TULISAN ARAB MELAYU DENGAN MENGGUNAKAN CARA ONLINE - Hidayatun Nur (Jurnal Educhild : Pendidikan dan Sosial, 2020)
Global conditions due to COVID 19 change things in life, including the way of learning which was initially carried out using face-to-face changes using online or online methods. This change also occurred in learning Malay Arabic Writing. In the Arabic Malay Writing course, online learning is something new. The purpose of this study was to determine the learning motivation of students in the online Malay Arabic Writing course. This research uses a descriptive quantitative method with a large sample of forty students. From the results of the study, it can be seen that the device that is widely used for online learning is android, the experience of learning Malay Arabic writing is generally at the elementary school level, the device used with the motivation to learn Malay Arabic writing online has no significant relationship, and the learning experience with the motivation to learn writing in Arabic Arab Malay online does not have a significant relationship.Kondisi global akibat akibat COVID 19 mengubah hal kehidupan termasuk dalam cara belajar yang pada awalnya dilaksanakan dengan menggunakan tatap muka berubah menggunakan cara online atau daring. Perubahan ini juga terjadi pada pembelajaran Tulisan Arab Melayu. Pada mata kuliah Tulisan Arab Melayu pembelajaran online merupakan hal yang baru. Tujuan penelitian ini untuk mengetahui motivasi belajar Peserta Didik pada matakuliah Tulisan Arab Melayu online. Penelitian ini menggunakan metode deskriptif kuantitatif dengan banyak sampel sebanyak empat puluh orang Peserta Didik. Dari hasil penelitian dapat diketahui perangkat yang banyak digunakan untuk belajar online adalah android, pengalaman belajar tulisan arab melayu pada umumnya pada jenjang sekolah dasar, perangkat yang digunakan dengan motivasi belajar tulisan arab melayu online tidak memiliki hubungan yang signifikan, dan pengalaman belajar dengan motivasi belajar tulisan arab melayu online tidak memiliki hubungan yang signifikan.